Developing an Instrument to Assess Physical Education Teachers’ Competencies in Using Fitness Monitoring to Promote Physical Literacy - Hossein Sepahvand; Bojan Leskošek; Kaja Meh; Sara Besal; Gregor Jurak (Education Sciences)
Background: Physical education teachers (PETs) play a vital role in fostering students’ physical literacy (PL). To leverage fitness monitoring as an efficient educational tool for students’ holistic development and lifelong physical activity, PETs must be proficient and competent in its implementation. This study aimed to create an instrument to evaluate teachers’ competencies essential for promoting PL through fitness monitoring. Methods: A Delphi study with 30 experts from 26 countries established content validity. Pilot testing on 339 PETs across Europe assessed psychometric characteristics using exploratory factor analysis and Cronbach’s alpha. Results: The Delphi study identified 13 core competencies, but construct validation revealed seven dimensions: (1) supporting cognitive learning, (2) encouraging positive feedback and learning climate, (3) understanding of fitness concept, (4) emotional support, (5) planning, (6) understanding of PL concept, (7) explaining learning objectives. Thus, the final instrument, the FitBack PET competency questionnaire, was designed with 27 items covering 7 competencies. The instrument exhibited high reliability, with Cronbach’s alpha exceeding 0.7 for six factors and the intraclass correlation coefficient of 0.94 for test–retest. Conclusions: The instrument’s development was successful, demonstrating high validity and reliability. The final version is publicly available, providing a practical tool for teacher training programs.